POTRET JURNAL ELEKTRONIK TERAKREDITAS BIDANG PERPUSTAKAAN DOKUMENTASI DAN INFORMASI DI INDONESIA - Rochani Nani Rahayu; Sensusiyati Sensusiyati (Central Library of Universitas Sebelas Maret, 2020)
Descriptive research on electronic journals in the field of library and information sciences in Indonesia, aims to determine 1) the number of accredited electronic journals, 2) journal publishers which are divided into a) state and private Islamic universities; b) public and private universities; c) non-tertiary institutions; d) professional associations; 2) City of published journals; 3) whether the journal site is active or not; 4) Frequency of journal publication and 5) Journal accreditation status. Data were collected from the data base http://issn.pdii.lipi.go.id/ and http://sinta.ristekbrin.go.id by searching using library keywords, documentation and information. Furthermore, the data were grouped according to research objectives. The results showed that the number of journals was 41 titles, published by 37 publishers. A total of 15 titles were published by state / private Islamic universities, followed by 14 titles by public / private universities, 7 titles by non-tertiary institutions, and 5 titles by professional associations. Journals are published in 21 cities, and Jakarta is in the highest position (19.51%), the National Library of the Republic of Indonesia is in the first rank as the largest journal publisher (3 titles). The most frequent publication of journals is twice per year (85.36%). Since March 1, 2020, as many as 31 sites are active (accessible), and the rest are inactive. A total of 13 journals have accredited status. The highest accreditation is SINTA 2 (3 titles). It is concluded that the electronic library library information journal as of March 2020 is known to be 41 titles, published by 37 publishers. Most publishers come from non-Islamic state universities and the National Library of the Republic of Indonesia is the largest publisher. Jakarta is the highest city of publication. Most of the frequency of publication of journals is twice per year, not all electronic journal websites can be accessed as of March 11, 2020, and based on the accreditation status it is known that there is no journal with SINTA 1 accreditation status.